La prolifération des cyanobactéries au Québec : une perspective de sciences sociales sur le risque et la gestion - Karine Dubé (Éditions en environnement VertigO, 2016)
Using a constructivist political ecology perspective, this exploratory qualitative research examines the social representations, attitudes and impacts that exist in relation to the phenomenon of cyanobacteria. Cyanobacteria are naturally occurring microorganisms found in most bodies of water ; certain species, especially when they are highly concentrated, release toxins that can pose a threat to population health. In Quebec, when the level of risk is considered serious, public health officials issue warnings concerning water-related activities and water consumption, but people do not always act in accordance with them. A qualitative study was undertaken with the aim of gaining a better understanding of the attitudes of citizens towards cyanobacteria and public health measures. It enabled us to identify both the meanings attached to this phenomenon – by drawing attention mainly on social representations of risk – and the other driving forces behind the attitudes and, in particular, towards compliance with measures prescribed by the authorities. Focus groups and semi-directed individual interviews involving several groups of social actors were conducted in 2009 and 2010 on Lake William, in the Missisquoi Bay and on Lake Roxton. Results illustrate coexistence of different social representations of the same phenomenon, which could modulate risk management process. This study points to the importance of considering natural phenomena such as the proliferation of cyanobacteria as socio-cultural constructs, because this approach can be applied to address the impacts of such phenomena from a different perspective and therefore improve management practices to reduce these impacts.